Pengaruh Pemahaman Sistem Akuntansi Keuangan Daerah, Kapasitas Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi terhadap Kualitas Informasi Laporan Keuangan Pemerintah Daerah (Studi Kasus pada Pemerintah Daerah Kota Yogyakarta) - Erawati, Teguh (AKMENIKA, 2018)
The research is to examine the influence of the understanding of local financial accounting system, capacity of human resource and the utility of information tecnology toward the quality of financial report information of yogyakarta government.The used data for the research is primer data. It is the result from questionnaires spreading. The respondence of this research is manager of financial report of yogyakarta local government. The questionnair is spread to 90 respondents, meanwhile that can be proccesd are 63 questionnaires. The method of sample taking is using purposive sampling. Analytic technique of data in this research is using double linier regretion technique.The result of regretion test shows that the local government financial accounting system understanding and the capacity of human resource are not influenced significantly to the quality of local government financial report information, meanwhile the utility of technology is influenced positively to the quality of local government financial report information.keyword: the understanding of local financial accounting system, capacity of human resource, the utility of information technology and quality of local government financial report information.